STATIC BALANCE OF PERSONS WITH INTELLECTUAL DISABILITIES, VISUAL IMPAIRMENT AND WITHOUT DISABILITIES - Klavina, Aija; Jekabsone, Ilze (European Journal of Adapted Physical Activity, 2014)
This study aimed to compare static balance of students with severe intellectual disabilities (SID), visualimpairment (VI) and non-disabled (ND) persons 18-24 years of age. Eleven students with VI, nine with SIDand eleven ND students performed the One-Leg Stance balance test (10s). The Digital Balance Analyzer(DBA) platform was used to measure the Balance Index (range from 0 "excellent balance" to 10 "very poorbalance"). Subjects performed tests in open and closed eyes conditions. On right leg with open eyes resultsindicated statistically significant differences between both groups of students with disabilities and nondisabledstudents (p < .05), while results between groups of students with disabilities were not significantlydifferent. The mean scores on the left leg with open eyes were not significantly different among the threegroups (p >.05). In tests on both legs with closed eyes significant difference was in mean results for studentswith VI (p <.05), while no differences were found for students with and without SID (p >.05). The mainfinding of this study was that static balance scores were inferior in VI group than in SID and ND group.Finally, all participants demonstrated significantly better static balance skills on right leg than on left leg.
Keywords: Static balance; visual impairment; intellectual disability